3D bioprinting of biomimetic skeletal muscle tissue model - Zhuang, Pei (Nanyang Technological University, 2020)
Skeletal muscle has the remarkable self-regeneration capability for minor injuries, yet massive muscle damage cannot be regenerated spontaneously and usually requires surgical interventions. The advances in tissue engineering technology have provided alternatives to build tissues with well-aligned muscle cells in both 2D and 3D. However, most strategies could only generate tissue models in micron-scale or with limited thickness, which are not suitable for volumetric muscle loss (VML). As a proof of concept, integration of 3D bioprinting technology and capillary action was performed to fabricate large 3D constructs for skeletal muscle tissue engineering. Firstly, a layer-by-layer ultraviolet assisted extrusion-based bioprinting technology was established to fabricate complex constructs with high aspect ratio using the gelatin methacryloyl-gellan gum (GelMA-GG) bio-inks. The results suggested that bio-inks with the viscosity lower than 0.124 Pa s at 37◦C were suitable for cell encapsulation and viscosity of 0.2 - 1.0 Pa s at 25◦C were bioprintable for complex constructs using layer-by-layer UV-assisted bioprinting strategy. The second part involved the development of suitable bio-inks and the investigation of the cell viability over the entire bioprinting process. Gelatin was introduced into the GelMA-GG composite bio-ink to endow the bio-ink with dynamic mechanical properties. The newly formulated bio-ink was recognized to be initially printable and subsequently cell favorable. This hydrogel can serve as a new bio-ink for cells that require stiff surroundings for attachment and softer substrates for growth. In addition, thick and complex tissue models may require a prolonged printing process. To better understand the cell behavior during the printing process, cell viability over the whole printing process was analyzed. Both C2C12 and human umbilical vein endothelial cells (HUVECs) were examined. The results provided a deep insight into the cell damage induced by shear stress and UV crosslinking. Lastly, the feasibility of fabricating large 3D skeletal muscle constructs with well-organized cells through the combination of 3D bioprinting and capillary action was demonstrated. Dual bio-inks (GMGAGG and gelatin) and co-culture (C2C12 and HUVECs) were incorporated. The parametric study including the effects of varied line spacing and different seeding density on cell alignment was performed. The suitable co-culture medium was optimized to maintain and support the growth of both C2C12 and HUVECs. The results of the co-culture study have identified that 30% HUVECs suffice to support the growth of C2C12. The immunofluorescence analysis has revealed the longitudinal myofiber formation in both constructs with C2C12 only and the co-cultured constructs. The results demonstrated the feasibility and efficacy of constructing 3D thick tissues in a mild and efficient manner.